Phenolic composition of wine from ’Cabernet Sauvignon’ grapes subjected to leaf removal at different timing in Southern Brazil Composic;ao fen61ica do vinho de uvas ’Cabernet Sauvignon’ submetidas a diferentes epocas de desfolha na regiao Sui do Brasil - Wurzl D.A. (2020)
© 2020. All Rights Reserved.The objective of this work was to evaluate the phenolic composition of wine from ‘Cabernet Sauvignon’ (Vitis vinifera) grapes subjected to leaf removal management at different timing, in a high-altitude region. The experiment was carried out in the 2015 and 2016 vintages, in a vineyard located in the municipality of Sao Joaquim, in the state of Santa Catarina, Brazil. The treatments consisted of different periods of leaf removal in the clusters, at five phenological stages - full bloom, buckshot berries, pea-sized berries, veraison, and 15 days after veraison -, and of a control without leaf removal. At harvest, 50 kg of each treatment were collected for winemaking. The contents of gallic acid, catechin, p-cournaric acid, vanillic acid, resveratrol, quercetin, rutin, and kaempferol were evaluated. The results showed the importance of leaf removal before veraison, to obtain wine with a higher concentration of phenolic compounds, which favors wine quality. The leaf removal management promotes the increase of gallic acid, vanillic acid, p-cournaric acid, resveratrol, quercetin, and kaempferol in wine. The early leaf removal before veraison results in increases in vanillic acid, p-coumaric acid, resveratrol, quercetin, and kaempferol. The wine made from grapes not subjected to leaf removal shows higher values of catechin and rutin.